Translation quality, use and dissemination in an Internet era: using single-translation and multi-translation parallel corpora to research translation quality on the Web - Miguel A. Jiménez-Crespo (JoSTrans: The Journal of Specialised Translation)
The Internet revolution is having a profound impact on the practice and theorisation of translation. Among the many changes induced by this revolution, this corpus-based study focuses on the impact of the immediacy afforded by the Internet on the fuzzy notion of translation quality. If this notion is understood as a relative construct due to economic and time constraints (Hönig 1998), increased time pressure entails inevitable compromises between access to information and translation quality. In order to research this issue, this paper contrasts the quality in a corpus of White House official translations of Obama´s speeches to a parallel corpus of similar translations released by online media immediately after their delivery. Following previous time-pressure studies (De Rooze 2003), an error-based quality analysis is used and the differences between both textual populations are quantitatively and qualitatively described. In a second stage, the quality of the translations under pressure is contrasted with their reuse or reposting on the WWW. The results of this analysis do not show a direct relationship between translation quality and the potential for use and subsequent reuse. Rather, there seems to be a direct relationship between translation reuse and the volume of traffic of the website in which a translation was posted. This study sheds some light on the uneven relationship between translation quality, time pressure enhanced by Internet immediacy and the impact of translated texts on receiving cultures.